OP0142 Rituximab in systemic sclerosis : safety and efficacy data from the eustar network. (12th June 2018) - Elhai, M.; Distler, O.; Smith, V.; Matucci-Cerinic, M.; Alegre-Sancho, J.J.; Truchetet, M.-E.; Braun-Moscovici, Y.; Iannone, F.; Chotchaeva, F.; Lescoat, A.; Siegert, E.; Castellví, I.; et al.
Abstract : Background: Few small-sized observational studies have suggested that rituximab might be a promising treatment in systemic sclerosis (SSc) Objectives: To evaluate the outcomes of SSc-patients receiving in routine care Rituximab Methods: Retrospective longitudinal multicenter observational study which included SSc-patients treated with rituximab upon the decision of their physician within the framework of EUSTAR. We interrogated the participating centres and EUSTAR database to determine epidemiological and clinical characteristics, the indication for initiating the treatment, and the following parameters at baseline and at the last visit under treatment: modified Rodnan Skin Score (mRSS), joint, lung and gastrointestinal involvements, treatment, laboratory tests and safety events. Results: 248 patients were included: 70 (28%) men, mean age: 51±13 years, mean disease duration: 7±7 years; 150 (65%) had diffuse cutaneous-SSc, 54% were positive for anti-topoisomerase and 71% had lung fibrosis. Overlap disease was noticed in 62 patients (26%) including 23 with rheumatoid arthritis. The indication for the treatment was lung involvement (56%) followed by articular (42%) and skin involvements (30%). At baseline, 175 patients were treated with steroids and 132 with DMARDs. Mean follow-up was 2.4 (±1.9) years. In the whole sample, mRSS decreased from 15±11 to 10±8 (p<0.01). For SSc-patients treated for lung with baseline FVC <70%, FVC improved from 56±9% to 59±12%; p=0.02. In patients with articular involvement (n=83), tender joint and swollen joint counts decreased from 9±7 to 4±6 and from 3±5 to 1±3, respectively (p<0.01). In the whole population, 45 patients could stop steroids and mean dose decreased from 10 mg to 7 mg in the other. During the follow-up, 78 (31%) patients had side effects including 35 (14%) with severe side effects leading to discontinuation of the treatment in 10%. Six deaths were recorded (1 heart failure, 1 sepsis, 2 respiratory insufficiencies, 2 sudden deaths). 76 patients had infection, requiring hospitalisation in 20 patients. Conclusions: In this study, skin, lung and joint involvement appeared to improve under rituximab. Infections and other severe adverse events were frequently reported. A comparative study including control patients from EUSTAR centres is ongoing. Disclosure of Interest: M. Elhai: None declared, O. Distler Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Novartis, Pfizer, Sanofi, Sinoxa and UCB in the area of potential treatments of scleroderma and its complications, V. Smith : None declared, M. Matucci-Cerinic: None declared, J. J. Alegre-Sancho : None declared, M.-E. Truchetet: None declared, Y. Braun-Moscovici: None declared, F. Iannone: None declared, F. Chotchaeva: None declared, A. Lescoat : None declared, E. Siegert : None declared, I. Castellví: None declared, P. Airò : None declared, S. Vettori: None declared, E. Hachulla: None declared, A. Erler : None declared, L. Ananieva : None declared, M. Krusche: None declared, F. López-Longo : None declared, J. Distler : None declared, N. Hunzelmann : None declared, A.-M. Hoffmann-Vold : None declared, V. Riccieri: None declared, V. Hsu: None declared, M. Pozzi: None declared, C. Ancuta : None declared, E. Rosato : None declared, C. Mihai: None declared, M. Kuwana: None declared, Y. Allanore Grant/research support from: Actelion, Bayer, Boehringer Ingelheim, ChemomAb, Genentech/Roche, Inventiva, Pfizer, Sanofi, Servier, in the area of potential treatments of scleroderma and its complications.